Analysis of The Influence of Competency, Motivation, and Work Environment on Employee Performance in The Library and Archives Service of the Bontang City Government - Badarita, Badarita; Irawan, Bambang; Kus, Indarto (Universitas Pancasakti, 2025)
This study investigates the influence of competence, work motivation, and the work environment on employee performance at the Bontang City Library and Archives Service. The research aims to analyze how these three internal factors interact to shape employee productivity, satisfaction, and commitment in a public sector setting. Employing a quantitative research approach with a causal-explanatory design, the study utilizes a structured questionnaire distributed to employees as respondents. Data were analyzed through statistical techniques, including correlation and regression analysis, to determine both partial and simultaneous effects of each variable on performance outcomes. The findings reveal that competence significantly enhances task effectiveness, motivation drives employee engagement and commitment, and a supportive work environment improves satisfaction and overall productivity. Collectively, these factors contribute to strengthening institutional performance and promoting good governance practices in local administration.